Development of E-Logistic Success Model in Indonesia - Rahman, Muhammad Luthfir; Sensuse, Dana Indra (Business Review and Case Studies, 2024)
Logistics companies in the world started to shift from traditional logistics business models to E-Logistics business models that benefited digitalization and Information Communication Technology. For the successful implementation of a system that implemented e-logistics, the success factors for adopting e-logistics needed to be studied in order to achieve efficient and effective e-logistics implementation. The purpose of this research was to build a successful model of E-logistics adoption. This study used a Systematic Literature Review to identify the success factors of e-logistics adoption, conducted interviews with experts for validation, and performed quantitative validation through questionnaires and was analyzed using the Spearman correlation test to see the relationship of each factor to the adoption of E-Logistics. This research succeeded in creating a successful model for E-Logistics adoption in Indonesia. The results of the Spearman correlation test showed that all hypotheses were accepted. This could be seen from the correlation value of each factor, which had a positive value towards E-Logistics adoption. The HBS factor had a value of +0.458, the FAO factor had a value of +0.481, the EIF factor had a value of +0.548, the OTD factor had a value of +0.499, the FDC factor had a value of +0.640, the GVS factor had a value of +0.598, the EPM factor had a value of +0.764, the ETC had a value of +0.601, the ECB factor had a value of +0.651, the WDS factor had a value of +0.844, the TIS factor had a value of +0.771, the TMS factor had a value of +0.590, and the FIS factor had a value of +0.498 on the success of E-Logistics adoption. All of the hypotheses were accepted, and it was hoped that the model in this research could become a standard and reference in the development of E-Logistics theory and the development of E-Logistics systems in Indonesia. Keywords: e-logistics, information technology, logistics, supply chain, systematic review